Quantative calcareous nannofossil biostratigraphy of Bay Akrotiri section (Cefallinia island, W. Greece). Tracing the gephyrocapsid size-trend in an early Pleistocene terrigenous sequence - TRIANTAPHYLLOU, M. V. (Bulletin of the Geological Society of Greece, 2018)
Bay Akrotiri section represents a thick terrigenous sequence laying along the southern part of Paliki peninsula (southwest Cefallinia). The data of the calcareous nannofossil quantitative analysis indicate that the studied sediments are ranging in terms of age between 1.95 Ma and 1.238 Ma approximately. The provided distribution patterns clearly depict an apparent evolutionary lineage close to the Plio/Pleistocene boundary, from small Gephyrocapsa placoliths to larger forms of gephyrocapsids.